STUDY ON FATIGUE LIFE IN FREQUENCY DOMAIN FOR BOGIE FRAME - ZHU Tao; XIAO ShouNe; YANG GuangWu; LIU JianShu (Jixie qiangdu)
Traditional bogie frame fatigue design uses the amplitude loads,which is significantly not inconsistent with random excitation suffered on the frame in actual operation. This method often leads to excessive fatigue strength of the overall frame and the anti-fatigue design in local structure insufficient. Firstly,the inverse Fourier transform was used to transform the stochastic process between time domain and frequency domain,and the correctness and feasibility of load history which proposed is verified by comparative analysis. Then,based on the inverse Fourier transform method and cubic spline differential method,rail vertical irregularity and longitudinal irregularity in displacement,velocity and acceleration power spectrum were given,respectively. Finally,the multi-point and multi-axis random vibration analysis of the bogie frame was processed,the real operating conditions of the structure were simulated,and the weak fatigue position of the structure was predicted. The results shows that the fatigue life calculation of the frequency-domain can be good used to predict the vibration fatigue,and provide an effective method for anti-fatigue design of bogie frame.